ABS composite material as well as preparation method and application thereof

A composite material using ABS and PCL resins with specific properties, combined with a spherical nucleating agent, addresses odor and stability issues in ABS materials, ensuring consistent fit and reduced stress in building blocks.

CN119161688APending Publication Date: 2024-12-20KINGFA SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411436176.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing ABS materials used in building blocks face issues with odor and unstable dimensional stability due to the use of low molecular weight lubricants, which can cause residual stress and inconsistent fit, especially in high-speed injection molding.

Method used

A composite material comprising ABS resin, PCL resin with specific viscosity-average molecular weight, and a spherical nucleating agent is formulated to enhance compatibility and reduce odor, with the PCL resin acting as a plasticizer and the nucleating agent accelerating crystallization and reducing residual stress.

Benefits of technology

The composite material achieves low odor and improved dimensional stability, allowing for consistent fit and reduced residual stress, making it suitable for applications like children's toys and household appliances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161688A_ABST
    Figure CN119161688A_ABST
Patent Text Reader

Abstract

The invention discloses an ABS (Acrylonitrile Butadiene Styrene) composite material as well as a preparation method and application thereof, and relates to the technical field of modified plastics. The invention provides an ABS (Acrylonitrile Butadiene Styrene) composite material. The ABS composite material comprises the following components in parts by weight: 60-95 parts of ABS resin, 5-40 parts of PCL (Polycaprolactone) resin and 0.1-1 part of a nucleating agent, the apparent viscosity of the ABS resin ranges from 15 Pa.s to 35 Pa.s, and the viscosity average molecular weight of the PCL resin ranges from 60000 to 100000; the nucleating agent is a spherical nucleating agent. The PCL resin with specific viscosity-average molecular weight, the ABS resin with specific apparent viscosity and the spherical nucleating agent are selected and combined, and the prepared ABS composite material is low in residual stress, good in dimensional stability and low in odor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified plastics, in particular to an ABS composite material and a preparation method and application thereof. Background Art

[0002] ABS material has the advantages of balanced rigidity, high gloss, and dimensional stability. It is widely used in household appliances and office equipment. In addition, due to its high gloss and bright colors, it is also widely used in toys. The above characteristics make ABS the mainstream material for children's plastic building blocks. For example, plug-in building blocks are concave and convex surfaces that match each other, and the dimensional stability of the building blocks is extremely high. If the concave and convex surfaces are too tight, the hand feel will be stiff, and if the concave and convex surfaces are too loose, the hand feel will be loose. At present, the measures taken by ABS building blocks to further improve the dimensional stability are generally to add lubricants to improve the fluidity of the system, thereby improving the dimensional stability of the ABS system. However, this system has two disadvantages: first, the lubricant is a low molecular weight substance and is prone to produce odor; second, if the lubricant is improperly selected, it is easy to produce residual stress after high-speed injection molding, resulting in unstable building block size and large changes in feel.

[0003] Therefore, an ABS composite material with low odor and good dimensional stability has broad application prospects. Summary of the invention

[0004] Based on this, the object of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide an ABS composite material with low odor and good dimensional stability.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an ABS composite material, comprising the following components in parts by weight: 60-95 parts of ABS resin, 5-40 parts of PCL resin, and 0.1-1 parts of nucleating agent; the apparent viscosity of the ABS resin is 15-35 Pa·s, the viscosity-average molecular weight of the PCL resin is 60000-100000; and the nucleating agent is a spherical nucleating agent.

[0006] The present invention selects a PCL resin with a specific viscosity average molecular weight and an ABS resin with a specific apparent viscosity to combine. The PCL resin can play a plasticizing role, so that the ABS resin can be easily molded under low shear, and the prepared ABS composite material has low residual stress and good dimensional stability. The present invention abandons the conventional scheme of using a lubricant to improve fluidity. The PCL resin with a specific viscosity average molecular weight and the ABS with a specific apparent viscosity are combined to form a composite material with good compatibility. At the same time, the PCL resin with a specific viscosity average molecular weight can reduce the odor generated after ABS injection molding. The inventor found in the actual experimental process that there are certain requirements for the amount of PCL resin. When the amount of PCL resin is too high, the crystallinity of PCL makes the dimensional stability of the prepared ABS composite material worse. When the amount of PCL resin is too low, the dimensional stability of the prepared ABS composite material is worse, and the odor is more obvious. The inventor found in the actual experimental process that the use of a spherical nucleating agent can, on the one hand, accelerate the crystallization rate and reduce the grain size; on the other hand, it can reduce the impact on the fluidity of the system, reduce residual stress, and further improve dimensional stability.

[0007] The ABS resin of the present invention is tested for apparent viscosity using method A capillary die according to ISO 11443-2005, "Plastics. Determination of fluidity of plastics by capillary and slot rheometers", and the test is performed at 240°C and a shear rate of 2000s. -1 The test equipment is the Rheograph 20 capillary rheometer of the German company GOETTFERT, with a barrel length of 230mm and a diameter of 15mm. The plunger length is 285mm and the diameter is 14.99mm. The die diameter is 1mm and the die height is 20mm. The ABS material must be dried in an oven at 80℃ for 4h before testing, and the sample must be preheated in the barrel for 5min before testing the apparent viscosity.

[0008] The viscosity average molecular weight of the PCL resin of the present invention is measured and calculated by an Ubbelohde viscometer. Alternatively, the viscosity average molecular weight of the PCL resin of the present invention is measured by an Ubbelohde viscometer at a test temperature of 25° C. using dichloromethane as a solvent, and is calculated using Schnell's viscosity formula.

[0009] Preferably, the weight percentage of the ABS resin in the ABS composite material is not less than 50%.

[0010] Optionally, the weight of the ABS resin is 60 parts, 61 parts, 63 parts, 65 parts, 68 parts, 70 parts, 71 parts, 73 parts, 75 parts, 78 parts, 80 parts, 81 parts, 83 parts, 85 parts, 88 parts, 90 parts, 91 parts, 93 parts, 95 parts, or any two of the range values; the weight of the PCL resin is 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts, 30 parts, 35 parts, 38 parts, 40 parts, or any two of the range values; the weight of the nucleating agent is 0.1 parts, 0.2 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 part, or any two of the range values.

[0011] Optionally, the apparent viscosity of the ABS resin is a range value of one or any two of 15Pa·s, 18Pa·s, 20Pa·s, 25Pa·s, 28Pa·s, 30Pa·s, 32Pa·s, 33Pa·s, and 35Pa·s; the viscosity-average molecular weight of the PCL resin is a range value of one or any two of 60,000, 70,000, 80,000, 90,000, and 100,000.

[0012] Preferably, the weight ratio of the ABS resin to the PCL resin is (70-80):(20-30).

[0013] The inventors found in actual experiments that the weight ratio of the ABS resin to the PCL resin further affects the dimensional stability of the prepared ABS composite material. When the weight ratio of the ABS resin to the PCL resin is (70-80): (20-30), the dimensional stability is better.

[0014] Preferably, the sphere-forming nucleating agent is at least one of glass microspheres, ceramic microspheres, and spherical quartz, and the particle size D50 of the sphere-forming nucleating agent is 5-25 μm. Further preferably, the particle size D50 of the sphere-forming nucleating agent is 5-20 μm.

[0015] Optionally, the particle size D50 of the spherical nucleating agent is in the range of one or any two of 5 μm, 8 μm, 10 μm, 11 μm, 12 μm, 15 μm, 16 μm, 18 μm, 20 μm, and 25 μm.

[0016] The inventors found in actual experiments that when the particle size D50 of the spherical nucleating agent is 5-20 μm, the dimensional stability of the prepared ABS composite material is better.

[0017] Optionally, the particle size D50 test method of the spherical nucleating agent is a laser method. Specifically, 3 g of filler is added to 500 mL of water, shaken in an ultrasonic instrument for 1 min, the dispersed sample is added, and the analyzer is placed in a Malvern laser particle size analyzer for sample injection testing. The laser wavelength is 630 nm, the scattering angle is 90°, the test time is 300 s, the correlator is low speed, the medium temperature is 21, the light intensity distribution type, and the CONTIN2 analysis mode is adopted.

[0018] Preferably, the ABS composite material further comprises 0.1-1.5 parts of an antioxidant, and the antioxidant is at least one of hindered phenols and phosphites.

[0019] Optionally, the hindered phenol antioxidant includes at least one of 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, and pentaerythritol tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl)propionate]; the phosphite antioxidant includes at least one of bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate, tetrakis(2,4-di-tert-butylphenol)-4,4-biphenyl diphosphite, and tris[2.4-di-tert-butylphenyl]phosphite.

[0020] In the present application, the ABS composite material can have a better anti-oxidation effect by controlling the type of antioxidant.

[0021] In addition, the present invention provides a method for preparing the ABS composite material, comprising the following steps: mixing the components in proportion and adding them into a twin-screw extruder, performing melt extrusion and granulation to obtain the ABS composite material.

[0022] Preferably, the processing temperature of the twin-screw extruder is 120-220° C., and the rotation speed is 300-600 rpm.

[0023] Furthermore, the present invention provides the application of the ABS composite material in the fields of household appliances, office equipment, and toys. Specifically, the present invention provides the application of the ABS composite material in air conditioners, televisions, copiers, printers, and plug-in building blocks.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention selects a PCL resin with a specific viscosity average molecular weight and an ABS resin with a specific apparent viscosity to combine, and the PCL resin can play a plasticizing role, so that the ABS resin can be easily molded under low shear, and the prepared ABS composite material has low residual stress and good dimensional stability. The present invention abandons the conventional scheme of using a lubricant to improve fluidity, and the PCL resin with a specific viscosity average molecular weight and the ABS with a specific apparent viscosity are combined to form a composite material with good compatibility. At the same time, the PCL resin with a specific viscosity average molecular weight can reduce the odor generated after ABS injection molding. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a diagram for plugging and unplugging building blocks. DETAILED DESCRIPTION

[0026] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.

[0027] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0028] ABS resin-1: apparent viscosity is 19 Pa·s, DG-MG94, Tianjin Dagu Chemical;

[0029] ABS resin-2: apparent viscosity is 22Pa·s, GP-35, INEOS Styrolution;

[0030] ABS resin-3: apparent viscosity is 35 Pa·s, DG-417, Tianjin Dagu Chemical;

[0031] ABS resin-4: apparent viscosity is 10Pa·s, D670, Guoqiao, Taiwan, China;

[0032] ABS resin-5: apparent viscosity is 49Pa·s, DG-MG29, Tianjin Dagu Chemical;

[0033] PCL resin-1: viscosity average molecular weight is 60000, Esun600C, Guanghua Weiye;

[0034] PCL resin-2: viscosity average molecular weight is 80000, Esun800C, Guanghua Weiye;

[0035] PCL resin-3: viscosity average molecular weight is 100000, Esun1000C, Guanghua Weiye;

[0036] PCL resin-4: viscosity average molecular weight is 50000, Esun500C, Guanghua Weiye;

[0037] PCL resin-5: viscosity average molecular weight is 120000, Esun1200C, Guanghua Weiye;

[0038] Nucleating agent-1: hollow glass microspheres, D50 5 μm, HM10, Saint-Laite;

[0039] Nucleating agent-2: hollow glass microspheres, D50 14 μm, HM30, Saint-Laite;

[0040] Nucleating agent-3: solid glass microspheres, D50 of 17 μm, MC30, Saint-Laite;

[0041] Nucleating agent-4: hollow glass microspheres, D50 is 25 μm, HS42, Saint-Laite;

[0042] Nucleating agent-5: flaky talc, D50 is 8μm, brand AH-1250N6, Longsheng Huamei;

[0043] The antioxidant is a composite of a commercially available hindered phenol antioxidant 1010 and a commercially available phosphite antioxidant 168 in a mass ratio of 1:1.

[0044] Examples and Comparative Examples

[0045] The components of the ABS composite material of the present invention are shown in Table 1 and Table 2. The preparation method of the ABS composite material comprises the following steps: mixing the components in proportion and adding them into a twin-screw extruder, melt extruding, and granulating to obtain the ABS composite material. The processing temperature of the twin-screw extruder is 120-220°C; the temperature of the first zone is 40°C, the temperature of the second zone is 180°C, the temperature of the third to fifth zones is 200°C-210°C, the temperature of the sixth to tenth zones is 220°C, and the rotation speed is 500rpm.

[0046] Performance Testing

[0047] (1) Odor test method: The test was conducted in accordance with the PV3900-2000 "Odor Test for Components in Automobile Interiors" standard of Shanghai Volkswagen: 20g of the composite material was placed in a 1L odor test bottle; then placed in an 80℃ oven for 2h, and after the bottle was taken out and cooled to 60℃, the odor level was evaluated according to the odor level standard in Table 1. The level between two levels can be represented by 0.5. The number of assessors was 5, and the average level was calculated. The smaller the average value, the lower the odor of the product.

[0048] Table 1

[0049] grade Odor description 1 Can't feel 2 Feel it, don't disturb 3 Noticeable but not intrusive 4 Disturb 5 Strong dislike 6 Intolerable

[0050] (2) Dimensional stability:

[0051] Modify the plastic into 2*4 plug-in building blocks, see attached Figure 1 The injection molding conditions are: barrel temperature 210℃, injection pressure 50MPa, injection speed 60cm 3 / s, 30min in the conditioning room for conditioning, the conditioning room conditions are (23±2)℃&(50±10)%RH. After conditioning for 4h, the inner cavity length of the building block is measured under the secondary element (see Figure 1 ), counted as L1; continue to adjust for 48 hours and re-measure the inner cavity length value, recorded as L2. The magnification of the secondary element in both measurements is 500 times. Dimension change rate = (L1-L2) / L1*100%, if it is within 0.2%, it is judged to be dimensional stable.

[0052] Table 1

[0053]

[0054]

[0055] Table 2

[0056]

[0057] It can be seen from the above table that by selecting ABS with a specific apparent viscosity and PCL with a specific viscosity-average molecular weight, and combining a spherical nucleating agent with a suitable particle size, a composite material with an odor level ≤3.5 and a dimensional change rate ≤0.2% can be prepared.

[0058] From the comparison of Examples 1-3 and Comparative Examples 1-2, it can be seen that the ABS resin with an apparent viscosity of 15-35 Pa·s, PCL resin, and a nucleating agent system can be used to prepare a composite material with an odor level of ≤3.5 and a dimensional change rate of ≤0.2%. The apparent viscosity of the ABS resin is too low, resulting in poor dispersion of PCL in the system and poor dimensional stability of the final composite material. The apparent viscosity of the ABS resin is too high, which has a great impact on the odor and dimensional stability of the composite material and cannot meet the requirements.

[0059] From the comparison of Example 1, Example 4-5, and Comparative Example 3-4, it can be seen that the PCL resin with a viscosity average molecular weight of 60000-100000, ABS resin, and a nucleating agent system can be used to prepare a composite material with an odor level of ≤3.5 and a dimensional change rate of ≤0.2%. The viscosity average molecular weight of the PCL resin is too low, resulting in a too fast crystallization rate, a large dimensional change rate, and poor dimensional stability. The viscosity average molecular weight of the PCL resin is too high, the fluidity is poor, the residual stress is high, the dimensional change rate is large, and the dimensional stability is poor.

[0060] From the comparison of Example 1, Examples 6-8, and Comparative Examples 5-6, it can be seen that the use of the ball-forming nucleating agent can accelerate the crystallization rate and reduce the grain size on the one hand; on the other hand, it can reduce the impact on the fluidity of the system, reduce the residual stress, and further improve the dimensional stability. At the same time, when the particle size D50 of the ball-forming nucleating agent is 5-20 μm, the dimensional stability of the prepared ABS composite material is better.

[0061] From the comparison between Example 1, Examples 9-11 and Comparative Example 7, it can be seen that, when the ABS resin, PCL resin and nucleating agent are used in specific amounts, a composite material with an odor level of ≤3.5 and a dimensional change rate of ≤0.2% can be prepared.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An ABS composite material, characterized in that: The invention comprises the following components in parts by weight: 60-95 parts of ABS resin, 5-40 parts of PCL resin and 0.1-1 parts of nucleating agent; the apparent viscosity of the ABS resin is 15-35 Pa·s, the viscosity average molecular weight of the PCL resin is 60000-100000; and the nucleating agent is a spherical nucleating agent.

2. The ABS composite material according to claim 1, characterized in that: The weight ratio of the ABS resin to PCL is (70-80):(20-30).

3. The ABS composite material according to claim 1, characterized in that: The sphere-forming nucleating agent is at least one of glass microbeads, ceramic microbeads, and spherical quartz, and the particle size D50 of the sphere-forming nucleating agent is 5-25 μm.

4. The ABS composite material according to claim 1, characterized in that: The ABS composite material further includes 0.1-1.5 parts of an antioxidant, and the antioxidant is at least one of hindered phenols and phosphites.

5. A method for preparing the ABS composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the components in proportion and adding the components into a twin-screw extruder, performing melt extrusion and granulation to obtain the ABS composite material.

6. The method for preparing the ABS composite material according to claim 5, characterized in that: The processing temperature of the twin-screw extruder is 120-220° C., and the rotation speed is 300-600 rpm.

7. Use of the ABS composite material according to any one of claims 1 to 4 in the fields of household appliances, office equipment and toys.

8. Use of the ABS composite material according to any one of claims 1 to 4 in air conditioners, televisions, copiers, printers, and plug-in building blocks.